A gene-based radiation hybrid map of the gilthead sea bream Sparus aurata refines and exploits conserved synteny with Tetraodon nigroviridis - Tsalavouta Matina; Senger Fabrice; Magoulas Antonios; Power Deborah M; Bargelloni Luca; Louro Bruno; Franch Rafaella; Sarropoulou Elena; Patarnello Tomaso; Galibert Francis; Kotoulas Georgios; Geisler Robert (BMC Genomics, 2007)
Abstract Background Comparative teleost studies are of great interest since they are important in aquaculture and in evolutionary issues. Comparing genomes of fully sequenced model fish species with those of farmed fish species through comparative mapping offers shortcuts for quantitative trait loci (QTL) detections and for studying genome evolution through the identification of regions of conserved synteny in teleosts. Here a comparative mapping study is presented by radiation hybrid (RH) mapping genes of the gilthead sea bream Sparus aurata, a non-model teleost fish of commercial and evolutionary interest, as it represents the worldwide distributed species-rich family of Sparidae. Results An additional 74 microsatellite markers and 428 gene-based markers appropriate for comparative mapping studies were mapped on the existing RH map of Sparus aurata. The anchoring of the RH map to the genetic linkage map resulted in 24 groups matching the karyotype of Sparus aurata. Homologous sequences to Tetraodon were identified for 301 of the gene-based markers positioned on the RH map of Sparus aurata. Comparison between Sparus aurata RH groups and Tetraodon chromosomes (karyotype of Tetraodon consists of 21 chromosomes) in this study reveals an unambiguous one-to-one relationship suggesting that three Tetraodon chromosomes correspond to six Sparus aurata radiation hybrid groups. The exploitation of this conserved synteny relationship is furthermore demonstrated by in silico mapping of gilthead sea bream expressed sequence tags (EST) that give a significant similarity hit to Tetraodon. Conclusion The addition of primarily gene-based markers increased substantially the density of the existing RH map and facilitated comparative analysis. The anchoring of this gene-based radiation hybrid map to the genome maps of model species broadened the pool of candidate genes that mainly control growth, disease resistance, sex determination and reversal, reproduction as well as environmental tolerance in this species, all traits of great importance for QTL mapping and marker assisted selection. Furthermore this comparative mapping approach will facilitate to give insights into chromosome evolution and into the genetic make up of the gilthead sea bream.